Meritocracy: pillar of direct fiscal contribution in Chilean Universities - Pablo Méndez Montenegro; Karime Chahuán-Jiménez; Christian Corvalán Rivera; Daniel Cáceres Palacios; Ricardo Espinoza Díaz (Research in Statistics, 2025)
Contributions made by States to universities are linked to funding formulas that reflect input and/or output indicators. These indicators determine the tasks universities must perform in terms of teaching, research, and outreach. Direct Fiscal Contributions (AFD) are allocated to universities belonging to the Council of Rectors of Chilean Universities (CRUCH) based on a meritocratic model that uses a multivariate normal distribution with variables including the number of students enrolled in undergraduate courses, full-time equivalent academics and academic staff, ANID-funded research projects, and Web of Science publications. The amounts allocated by the AFD between 2006 and 2019 were taken into account for these variables. Therefore, it is empirically concluded that there is no meritocracy, meaning that some universities have more students, publications, and research projects, yet receive fewer contributions.